MR Safe Robotic Manipulator for MRI-Guided Intracardiac Catheterization - Lee,KH; Fu,KCD; Guo,Z; Dong,Z; Leong,MCW; Cheung,CL; Lee,APW; Luk,W; Kwok,KW (IEEE/ASME Transactions on Mechatronics, 2018)
This paper introduces a robotic manipulator to realize robot-assisted intracardiac catheterization in magnetic resonance imaging (MRI) environment. MRI can offer high-resolution images to visualize soft tissue features such as scars or edema. We hypothesize that robotic catheterization, combined with the enhanced monitoring of lesions creation using MRI intraoperatively, will significantly improve the procedural safety, accuracy, and effectiveness. This is designed particularly for cardiac electrophysiological (EP) intervention, which is an effective treatment of arrhythmia. We present the first MR Safe robot for intracardiac EP intervention. The robot actuation features small hysteresis, effective force transmission, and quick response, which has been experimentally verified for its capability to precisely telemanipulate a standard clinically used EP catheter. We also present timely techniques for real-time positional tracking in MRI and intraoperative image registration, which can be integrated with the presented manipulator to im prove the performance of teleoperated robotic catheterization.